Synergistic antibacterial mechanism of sucrose laurate combined with nisin against Staphylococcus aureus and its application in milk beverage. (15th March 2022) - Ning, Yawei; Hou, Linlin; Ma, Mengge; Li, Mingrui; Zhao, Zhongqing; Zhang, Dongchun; Wang, Zhixin; Jia, Yingmin
Abstract: Sucrose laurate (SL) is a dual-functional additive with emulsifying and antibacterial activities. The synergistic antibacterial mechanism of SL and nisin were studied against Staphylococcus aureus . Alkaline phosphatase and peptidoglycan assays showed that SL and nisin could synergistically disrupt the integrity of cell wall by blocking the synthesis of peptidoglycan. Fluorescence spectroscopy and flow cytometry analysis revealed that SL and nisin synergistically depolarized the membrane potential, inhibited the Na + K + and Ca 2+ Mg 2+ -ATPase activities on cell membrane, triggered K+ leakage, and damaged the permeability and integrity of cell membrane. SEM and TEM observations further exhibited obvious morphological changes, structural disruption and cytoplasmic leakage. Gel retardation and fluorescence spectroscopy analysis suggested that SL and nisin synergistically influenced the protein and genomic DNA. Finally, the synergistic preservative effect of SL and nisin was evidenced in real food system of milk beverage. This research could provide the insights into broadening the application of SL in food industry. Highlights: SL as a bifunctional additive shows synergistic antibacterial effect with nisin against S. aureus. The synergistic antibacterial mechanism was elucidated from multiple targets. The synergistic preservative effect of SL and nisin was evidenced in milk beverage. This study could provide evidence to broaden the application of SL in food industry.